Self-employment in times of crisis: The case of the Spanish financial crisis - Sergio A. Contreras (Economies, 2019)
While some researchers have suggested that the self-employment (SE) sector is a haven during a financial crisis, others believe that SE is not necessarily the desired outcome, but an indicator that the labor market is tightening for some groups. Few researchers have compared the SE sector before and after the occurrence of a significant financial crisis, especially in developed countries. This paper analyzes the determinants of entry into self-employment during the 2008 Spanish Crisis. Using data from the Encuesta de Presupuesto Familiar (EPF), results show that although the rate of SE did not experience a significant change during this time, the crisis affected people differently based on gender, with females being more affected than males. Results also suggest differences between Comunidades Autonomas in how the self-employment sector behaved during the crisis.
Keywords: J21; G01; L26; 330; financial crisis; household determinants; self-employment